KAITAN VANDALISME DENGAN KARAKTER SISWA DAN PEMELIHARAAN FASILITAS SEKOLAH DI MAN 4 PEKANBARU - Intan Nuraini; Sindy afrianti; Maisya Ratul Aini; Harnum Lismaawati; Feby Vidya Cornella Amanda; Fatimah A-Zahra; Nayla Gusri Wulandari; Aditya Rifandi; Rizki Dinda Sarmita Harahap; Hambali (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Vandalism is one of the negative behaviors still found in some school environments; it causes damage to facilities and disrupts the learning process. This study aims to identify the types of vandalism that occur in schools, the factors that cause them, and the preventive measures that can be implemented. This study employs a qualitative approach using observation, interviews, and documentation at MAN 4 Pekanbaru. The findings of the study indicate that the most common forms of vandalism are scribbling on desks, chairs, and classroom walls, as well as damaging other school facilities. Factors influencing these actions include the social environment, family circumstances, a lack of supervision from school authorities, and students’ desire to gain recognition from their peers. To prevent vandalism, it is necessary to enhance character education, provide guidance on school regulations, enforce sanctions, and implement positive activities that channel students’ creativity. This study emphasizes that collaboration between the school, parents, and the surrounding community is crucial for reducing acts of vandalism and creating a neat and supportive learning environment.